Pemanfaatan Video Youtube Berbahasa Inggris untuk Meningkatkan Keterampilan Mendengar di PKBM Paket C Kota Banjarmasin - M. Arbain; Hartatya Novika; M. Fikri Haq; Andrea Revaz (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service project aimed to implement and evaluate the effectiveness of using English-language YouTube videos to improve listening skills at Package C Community Learning Centers (PKBM) in Banjarmasin City. Listening skills have been identified as a major challenge for students at PKBM due to limited exposure to authentic materials and real-world language. This research utilized a pre-experimental design with a one-group pretest-posttest format involving 30 students from a local PKBM. The implementation stages included interactive lectures, YouTube video screenings, followed by discussions and question-and-answer sessions, with the effectiveness assessed through pretests and posttests. The quantitative results revealed a significant improvement in listening comprehension, with the average listening score increasing from 82.9 in the pretest to 86.7 in the posttest, reflecting a positive impact of the intervention. In addition to the quantitative results, the qualitative data highlighted high levels of student engagement and motivation throughout the learning process. Many students expressed that the YouTube videos made the content more relatable and enjoyable, which contributed to a deeper understanding of the material. This suggests that the use of YouTube videos is not only effective in enhancing listening skills but also fosters a more interactive and student-centered learning environment, making the learning experience more relevant to the needs of non-formal learners. The study concludes that YouTube videos are a promising and innovative tool for improving English language teaching at PKBM, providing accessible and engaging resources that can bridge the gap between formal and informal learning environments, helping students connect better with the material.